Fatigue-resistant and super-tough thermocells - Lili Liu; Ding Zhang; Peijia Bai; Yanjie Fang; Jiaqi Guo; Qi Li; Rujun Ma (Nature Communications)
Abstract Wearable thermocells offer a sustainable energy solution for wearable electronics but are hindered by poor fatigue resistance, low fracture energy, and thermal inefficiencies. In this study, we present a high-strength, fatigue-resistant thermocell with enhanced thermoelectric performance through solvent exchange-assisted annealing and chaotropic effect-enhanced thermoelectric properties. The mechanical strength and toughness are improved by forming macromolecular crystal domains and entangling polymer chains. Guanidine ions, with strong chaotropic properties, optimize the solvation layer of redox ion couple, boosting thermoelectric efficiency. Compared to existing anti-fatigue thermocells, the current design exhibits a 20-fold increase in mechanical toughness (368 kJ m-2) and a 3-fold increase in Seebeck coefficient (5.4 mV K-1). With an ultimate tensile strength of 12 MPa, a fatigue threshold of 4.1 kJ m-2, and a specific output power density of 714 μW m-2 K-2, this thermocell outperforms existing designs, enabling more reliable and efficient wearable electronics and stretchable devices.